Liberdades fundamentais e regionalização: reificação das relações de trabalho nos processos de integração econômica - Santos, Fabrizio Cândia dos (2014)
This work aims to analyze the legal regulation of labor relations taken in the core of regionalization processes undertaken through economic integration. We intend to demonstrate that the fundamental freedoms upon which are laid down the economic integration, in particular the free movement of workers, are not human freedoms, but derivation of the reification of human relations. Although the main backdrop is the MERCOSUR, other regionalization scenarios are also part of the analysis. To make the diagnosis of the legal texts of economic integration of MERCOSUR, it starts from the Lukacsian conception of reification, using a critical perspective on regulatory texts that rule the labor relations in this economic bloc. Therefore, concepts of Marxian alienation and Weberian rationalization lead to understanding of this analysis. There is still an approach from a historical perspective about the formation of rights reified as a result of the implementation of the capitalist and its regional and global expansion.